Electrical properties of sulfonated polyaniline (Span) and polyaniline (Pani) polymers grown on conventional and high index GaAs substrates - Jameel, Dler Adil (2016)
The electrical properties of sulfonated polyaniline (SPAN) and polyaniline (PANI) grown on both conventional (100) and high Miller index GaAs surfaces are investigated. These devices were electrically characterized using Current-Voltage (I-V), Capacitance-Voltage (C-V), Capacitance-Frequency (C-F), Capacitance-Conductance-Frequency (C-G-F), Deep Level Transient Spectroscopy (DLTS), and Laplace DLTS measurements in the temperature range 20 – 440 K. Electrically active defects are generated at/near the interface and away from the interface with energy levels deep in the bandgap of the materials. These defects considerably affect the electrical and optical properties of the devices. This thesis reports the effect of n-type GaAs substrate orientation, namely (100), (311)A and (311)B, on the electrical properties of sulfonated polyaniline (SPAN)/GaAs heterojunction devices. It was found that the interface state density (Dit) of SPAN/(311)B GaAs samples is lower than that of (100) and (311)A GaAs devices. This behaviour is attributed to the effect of crystallographic orientation of the substrates, and was confirmed by DLTS results as well. In addition, the inhomogeneity of the interface between various GaAs substrates and SPAN is investigated in terms of barrier height and ideality factor by performing I–V measurements at different temperatures (20–420 K). The I–V results indicate that the value of the rectification ratio (IF/IR) at 0.5 V is higher for SPAN/(311)B GaAs samples than for SPAN/(100) GaAs and SPAN/(311)A GaAs samples. Moreover, the barrier height decreases and the ideality factor increases with decreasing temperature for all three heterostructure devices.